Analisis Prediksi Financial Distress Atas Kinerja Keuangan PT. Wijaya Karya (Persero) Tbk Periode 2014 - 2023 - Lucky Lukman; Rosmegawati Rosmegawati; Arni Kurniati; Suhikmat Suhikmat Suhikmat; Sumihar M. L. Tobing (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The problem of accumulating debt burdens that entangle a number of state-owned enterprises in the construction sector or BUMN Karya is suspected to arise due to internal problems in governance. This situation is exacerbated by the burden of project assignments from the government that are not based on careful planning. This increase in debt occurred because the government provided assignments without participating in providing capital, so that each BUMN Karya sought other sources of funding, one of which was by increasing debt. The liabilities that burden PT Wijaya Karya (Persero) Tbk (WIKA) today are the result of the massive expansion of works financed by loans. The increase in WIKA's debt burden is due to the existence of pre-financing projects, where the payment scheme will be carried out after the project is completed. The payment scheme encourages an increase in the amount of company debt as capital for operational activities. The purpose of this study is to see and predict the extent to which financial performance affects financial distress at WIKA. The results showed that Return on Assets has a significant and positive effect on the occurrence of financial distress (Interest Coverage Ratio) and Current Ratio, Debt to Equity Ratio and Operating Cashflow have a significant and negative effect on the occurrence of financial distress (Interest Coverage Ratio).